Utilisation of Cariogram software to educate patients on caries risk assessment / Ikmal Hisham Ismail … [et al.] - Ismail, Ikmal Hisham; Kamarulzaman, Marlena; Abd Rahman, Hayati; Mukhtar, Ili Mazlina; Kipli, Norhysam (Research Innovation Business Unit, 2014)
Cariogram is a new and interactive method in dentistry, showing how the contributing factors of caries may interact. It was first made available on-line as a Windows-based system, and only recently the Mac version can be downloaded free. Objectives: The objective of this project is to implement this method to the staff and dental students of Faculty of Dentistry, UiTM. To gauge whether there will be better acceptance by the dental staff and students in line with the current trend of blended learning. A part of students’ interactive learning to enhance communication skills especially student patient interaction. To customize to our local custom and sensitivities to suit our patients needs. This will shorten the time for the operator to carry-out caries risk assessment when compared with the manual pen and paper method. The outcome of the print-out will be more interactive as well as effective. This will also facilitate the follow-up and monitoring of patient’s caries progression hence prevention. This will allow a prototype to be developed as applications suitable to run on tablet PCs.